Corporate Responsibility Due to Nickel Mine Exploitation Activities - Nur Bintang Alfina Laila; Frans Simangunsong (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This study aims to determine corporate responsibility for the impact of environmental pollution due to nickel mining activities. The research method used is the normative juridical method by collecting data sourced from literature studies, namely through a legal approach. In nickel mining exploitation activities it is known that it can cause environmental pollution, namely river, air, soil erosion, sedimentation of excavated remains. mining, decreased agricultural productivity around the mining areas, damage to flora and fauna, no health empowerment, no improvement in health infrastructure and changes in community behavior/norms around of the community around the mining areas. In addition, legal protection for the community must be enforced so that the rights of the community are not violated due to the exploitation of nickel mining that violates the provisions.